Invitation to the Triune Conversation: Explorations of Prayer through the Theology of Robert Jenson. (December 2013) - Henry, James Daryn
Abstract This paper attempts to contribute to our understanding of prayer through an engagement with its crucial role in the systematic thought of Robert Jenson. I present prayer as our invitation to the triune conversation. Developing some of Jenson's categories, I work to show that a Christian understanding of prayer connects to a spectrum of systematic loci, especially creation and anthropology, the sacraments and ecclesiology, mission and eschatology. In these three modes, the anthropological, the ecclesial and the eschatological, prayer enters into the ultimate conversation that animates the world through faith, love and hope. This paper concludes by arguing that such an account of prayer, if authentic, supports a contemporary retrieval of the cataphatic dimension of theology.